Translation, cross-cultural adaptation and validation of the revised-Skin Management Needs Assessment Checklist questionnaire in Malay language - Deena @ Clare Thomas; Chui, Ping Lei; Abqariyah Yahya; Yap, Jiann Wen (Elsevier, 2022)
Introduction: Pressure injury (PI) related knowledge can be used as an outcome indicator of a PI education program. In Malaysia, no scale has been translated and validated for measuring PI-related knowledge among patients with a PI. Aim: The purpose of this study was to cross-culturally adapt, translate and determine the validity and reliability of the Malay version of the revised-Skin Management Need Assessment Checklist (revised-SMnac). Method: The instrument was initially written in English and translated into the Malay language. The internal consistency, construct validity, and test-retest reliability were examined after the item and scale’s cross-cultural equivalence and content validity were evaluated. Construct validity was determined through the administration of the instrument amongst 170 hospitalised patients with a PI. Content validity index (CVI) was further determined through validation by a panel of five wound care experts. The instrument’s stability was determined by the test-retest model with a two-week interval. Results: The content validity of the item-CVI (I-CVI) was >79%, indicating that all 17-items were appropriate, while the scale-CVI (S-CVI) of >0.83 indicated an acceptable scale. The Cronbach’s Alpha was .994 indicated good internal consistency. Test-retest showed a good intra-class correlation coefficient, ICC = 0.955 with 95% CI [0.992–0.996]. Conclusions: The Malay version of the revised-SMnac demonstrated to be a valid and reliable tool to measure PI-related knowledge among the Malay-speaking patient population in Malaysia. The tool is recommended for use to measure the effectiveness of education programs related to PI care in future studies.